2015
DOI: 10.5152/eurasianjmed.2015.78
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Hand Hygiene Adherence at a Private Hospital in Turkey

Abstract: Objective: Nosocomial infections are the main problems rising morbidity and mortality in health care settings. Hand hygiene is the most effective method for preventing these infections. In this study, we aimed to investigate the factors related with hand hygiene adherence at a private hospital in Turkey. Materials and Methods:This study was conducted between March and June 2010 at a private hospital in Turkey. During the observation period, employees were informed about training, then posters and images were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 7 publications
2
21
0
5
Order By: Relevance
“…Only one of the included studies focused on a single professional group: nurses (7) . It should be noted that adherence to hand hygiene was higher among trained professionals than among untrained ones (76% versus 63%; p<0.005), and that antiseptic solutions were used when hand washing was not possible (9) . In the same line of thought, other authors have also reported an increase in the adherence to hand hygiene from Chart 2 -Description of the selected studies…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Only one of the included studies focused on a single professional group: nurses (7) . It should be noted that adherence to hand hygiene was higher among trained professionals than among untrained ones (76% versus 63%; p<0.005), and that antiseptic solutions were used when hand washing was not possible (9) . In the same line of thought, other authors have also reported an increase in the adherence to hand hygiene from Chart 2 -Description of the selected studies…”
Section: Discussionmentioning
confidence: 94%
“…Some authors (8) have analyzed the hand hygiene procedure ("five moments" for hand hygiene (5) ). According to these studies, after the training program, adherence was higher in steps 3 and 4 (self-protection) (8)(9) and lower after aseptic procedures (8) and after touching patient surroundings (10) . Similarly, the authors of another study observed that only 47% of the professionals washed their hands before touching the patient and that 70% washed their hands after touching the patient (6) .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations